Education and Attitudes Toward Migration in a Cross Country Perspective - Borgonovi, Francesca; Pokropek, Artur (Frontiers in Psychology, 2019)
The paper examines the dynamics of native populations’ opposition to migration and the role of education in shaping such opposition in European countries using data from the last four editions of the European Social Survey between years 2010 and 2016. We examine both the direct association between education and opposition to migration as well as the mediated association that occurs through feelings of threat. We test for measurement equivalence across countries and years of the two latent constructs in our analyses (opposition to migration and feelings of threat) by applying sequential methods used in alignment optimisation to identify partial equivalence and check the level of approximate measurement invariance using BSEM modelling. Our results indicate that the opposition to migration and the feelings of threat scales achieve metric invariance but not scalar invariance in cross-country comparisons. At the substantive level, our findings suggest that better educated individuals express lower opposition to migration than the poorly educated and that as much as 60% of education differentials in opposition to migration are due to the medated effect through feelings of threat. The high degree of heterogeneity in associations both across countries and over time are, in part, explained by the presence of foreign-born populations and living standards in a country and time point.